Aerial oxidation of coal-analytical methods, instrumental techniques and test methods: A survey - Sen R.; Srivastava S.K.; Singh M.M. (My University, 2025)
Aerial oxidation of coal particularly atmospheric oxidation of coal is mainly responsible for self heating of coal and deterioration of most of its useful technological properties like calorific value, floatability and caking properties. A lot of work has been done over the years to understand the exact mechanism of the processes responsible for this phenomenon. This literature survey attempts to list and describe various analytical techniques, both chemical and instrumental, standard tests and novel experimental procedures applied by various authors to study the different aspects of this phenomenon.